Specific features of African swine fever control activities in China - M. D. Lozovoy; S. V. Shcherbinin; A. K. Karaulov (Ветеринария сегодня)
African swine fever is a highly contagious viral disease of pigs; however, no vaccines are available to control it. Currently the disease causes significant economic damage in many countries. The Republic of China is the first country in Southeast Asia, which officially reported the African swine fever outbreak in 2018. The disease further spread to all provinces of the country with 200 outbreaks in domestic pigs and 10 outbreaks in wild boar in total; herewith the overall population of pigs de-creased dramatically, approximately by 180 million animals. Following the confirmation of the first African swine fever outbreak, the PRC Ministry of Agriculture and Rural Affairs launched the “African Swine Fever Contingency Plan and Emergency Response”, w hich facilitated the disease eradication and already by 2023, no new infection outbreaks had been reported. The country with the largest swine population in the world achieved rather moderate spread rates if compared to Europe.In addition, the virus strains, which circulated in the Chinese territory, were genetically diverse and different in virulence, leading to a wide range of clinical signs manifested by diseased animals. Such aspects were supposed to complicate the eradication measures, but instead, they proved their effectiveness. The experience gained from the disease control in China is most certainly of interest for the Russian Federation, infected with African swine fever since 2008.